## Expand (3 – 2x)6. What is the coefficient of the sixth term?

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

To expand (3 – 2x)^6 use the binomial theorem:

(x + y)^ n = C(n,0) x^ny^0 + C(n,1)x^(n-1) y + C(n,2)x^(n-2) y^2 + …+ C(n,n+1)xy^(n-1) + C(n,n)x^0y^n

So, for x = 3, y = -2x , and n = 6 you get:

(3 – 2x) ^6 = C(6,0)(3)^6 + C(6,1)(3)^5 (-2x) + C(6,2) (3)^4 (-2x)^3 + C(6,3) (3^3) (-2x)^4 + C(6,4)(3)^2 (-2x)^4 + C(6,5) (3) (-2x)^5 + C(6,6) (-2x)^6

So, the sixth term is C(6,5)(3)(-2x)^5 = 6! / [5! (6-5)! ] * 3 * (-2)^5 x^5 = – 6*3*32 = – 576 x^5.

The coefficient of that term is – 576.

Answer: – 576